The Effect of Ageing on Physical and Chemical Properties of Asphalt Cement - Abdul-Karim Mohammed, Abdul-Halim; Morshed, Khalid (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Two grades of paving asphalt with penetration of 46 and 65 are studied for determining changes in their physical and chemical properties caused by ageing. The ageing process has been conducted on two petroleum paving asphalt cement using thin film oven test at 150, 163 and 175 C, and ageing time 5, 10,15, 20, 25 and 30 hours. The effect of ageing time and temperature on penetration, kinematic viscosity, softening point, solubility in trichloroethylene, heat loss and changes in chemical composition are investigated. The results of thin film oven test process indicte that the asphaltenes concentration of all aged asphalt increases with increasing ageing time, while the opposite was observed for polar-aromatic and naphthene-aromatic. The saturate of low penetration grade asphalt is higher than that for high penetration grade asphalt and remained unchanged with ageing time. Th kinematic viscosity and softening point seem to increase with increasing ageing time, while the penetration decreases with increasing ageing time. The DI of aged asphalt inreases with increasing ageing time.